2018
DOI: 10.1111/jan.13719
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress symptomatology following exposure to perceived traumatic perinatal events within the midwifery profession: The impact of trait emotional intelligence

Abstract: Approximately one-fifth of midwives were experiencing posttraumatic stress symptoms at clinically significant levels. Trait emotional intelligence may protect against posttraumatic stress symptoms by supporting resilience, while enabling midwives to remain empathic. The negative correlation between resilience and empathy needs careful consideration by policy makers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…This study found that one of every five students met all criteria for posttraumatic stress disorder. Nightingale et al 21 and Beck et al 17 reported similar outcomes with rates of 20% and 36%, respectively.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…This study found that one of every five students met all criteria for posttraumatic stress disorder. Nightingale et al 21 and Beck et al 17 reported similar outcomes with rates of 20% and 36%, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…This study found that one of every five students met all criteria for posttraumatic stress disorder. Nightingale et al 21 and Beck et al 17 reported similar outcomes with rates of 20% and 36%, respectively. Contrary to our results, Sheen et al 14 and Cohen et al 8 found lower rates (5% and 16%, respectively).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Furthermore, grief counselling and better communication skills may provide more coping strategies, as one study found with healthcare workers experiencing less anxiety, increased confidence, and better relationship skills [ 54 ]. A supportive organizational ethos and change in culture from ‘blame’ to support would assist midwives in adjusting, minimizing psychological distress, and being better equipped to provide quality care [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%